2003
DOI: 10.1159/000072327
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback and Pelvic Floor Exercises for the Rehabilitation of Urinary Stress Incontinence

Abstract: We investigated the effectiveness of pelvic floor muscle (PFM) exercises or biofeedback for the treatment of urinary stress incontinence (USI). Fifty patients with USI were included in this randomized, controlled, prospective study. Twenty patients were taught PFM exercises via digital palpation and instructed to perform regularly as home program. The second group of 20 patients had PFM exercises via biofeedback three times a week for 2 months. The third group of 10 patients did not have any exercises. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0
14

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 19 publications
1
105
0
14
Order By: Relevance
“…Morkved e Fjortoft (29) compared women with SUI who had performed PF functional training exercises with women who had been trained with biofeedback, and observed 58% improvement in women who had used biofeedback and 46% in those who had only exercised. Aksac et al (30) also studied the effects of perennial exercise and biofeedback, and observed improved strength in both groups; however, there was greater gain in the group trained with biofeedback.…”
Section: Methodsmentioning
confidence: 99%
“…Morkved e Fjortoft (29) compared women with SUI who had performed PF functional training exercises with women who had been trained with biofeedback, and observed 58% improvement in women who had used biofeedback and 46% in those who had only exercised. Aksac et al (30) also studied the effects of perennial exercise and biofeedback, and observed improved strength in both groups; however, there was greater gain in the group trained with biofeedback.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies were eligible [14][15][16][17][18] , which included 250 women, 126 in the PFMT groups and 124 in the PFMT, in addition to biofeedback groups. One of them 15 was not included in the meta-analyses for some of the outcomes because its groups were heterogeneous at the beginning of the study, and the use of final measures only in the pooled estimates would not take this initial difference between groups into consideration.…”
Section: Pfmt Versus Pfmt Plus Biofeedbackmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37] At least 2 systematic reviews evaluated PFM training using biofeedback measurement. 38,39 Although PFM training for urinary incontinence is considered Level 1 scientific evidence, Latthe, Foon and Khan identified weaknesses in the methodology of the studies; they claim that the studies lack the power to produce reliable results.…”
Section: The Evolution Of Kegel Exercisementioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37] It is clear that there is no consensus on the amount of exercise required to improve PFM function. Over time, while different modalities and training protocols have been adopted, the most common approach is to use either PFM contraction exclusively, or in association with increased levels of overall physical activity.…”
Section: The Evolution Of Kegel Exercisementioning
confidence: 99%